A CRIANÇA E SEU ESPAÇO: UMA LEITURA SOBRE ARQUITETURA ESCOLAR E OS IDEAIS PEDAGÓGICOS - Tammy Yoshisato; Arlete Maria Francisco (Universidade do Oeste Paulista, 2015)
The first contact the child has with the outside world it is through the school because it is in the school ambience, that are created the first social relationships and acquired the first scientific knowledge. And it is not only the pedagogical proposal that will provide for the child the learning, but the space where he is inserted also has a great influence, enabling new experiences. This work aims to study the relationship between political and pedagogical ideals and school architectural typologies, from the Republic to the present day. The methodology starts of the research about educational ideals, from the available literature, and takes a reading of the plants of school buildings by graphic reading. It is concluded that the school space has evolved since the nineteenth century, however, the attention with the playfulness of space facing for child has not reached a solution that increases a quality of education in public schools in Brazil.